2005
DOI: 10.1148/radiol.2343031366
|View full text |Cite
|
Sign up to set email alerts
|

Posterior Cul-de-Sac Obliteration Associated with Endometriosis: MR Imaging Evaluation

Abstract: These results suggest that use of the described MR imaging findings may enable diagnosis of posterior cul-de-sac obliteration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
75
0
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(81 citation statements)
references
References 24 publications
2
75
0
4
Order By: Relevance
“…These include angulation of bowel loop, skip of bowel diameter, elevation of the posterior vaginal fornix, posterior displacement of the uterus, ovaries, or both, loss of fat planes between the structures, hidrosalpinx, and loculated fluid collection. Kataoka et al [40] reported a mean sensitivity of 77.8%, a mean specificity of 50.0%, and a mean accuracy of 76.3% for the detection of adhesions.…”
Section: Magnetic Resonance Imaging Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…These include angulation of bowel loop, skip of bowel diameter, elevation of the posterior vaginal fornix, posterior displacement of the uterus, ovaries, or both, loss of fat planes between the structures, hidrosalpinx, and loculated fluid collection. Kataoka et al [40] reported a mean sensitivity of 77.8%, a mean specificity of 50.0%, and a mean accuracy of 76.3% for the detection of adhesions.…”
Section: Magnetic Resonance Imaging Evaluationmentioning
confidence: 99%
“…Magnetic resonance imaging MRI can evaluate various signs of involvement of endometriosis in this region: (1) presence of macroscopic endometriosis implants (>5 mm); (2) indirect signs of adhesions, such as disappearance of the fat tissue plane separating the different structures; (3) direct signs of adhesions are well displayed on T2 -weighted imaging as hypointense bands, with variable thickness that result in stretching and distortion of the surrounding organs; (4) uterosacral ligament involvement is suspected in cases of increased and inhomogeneous thickness associated with abnormal arciform appearance; (5) presence of specific signs of posterior cul-de-sac obliteration: retroflexed uterus; tethered appearance of the rectum in direction of the uterus; strands between the uterus and intestine; fibrotic plaque covering the serosal surface of the uterus and elevated posterior cervical fornix [40]; and (6) evaluation of signal intensity of endometriosis lesions is required as it varies according to the microscopic characteristics of the ectopic tissue. Signal intensity can present three main patterns: (1) hypointense signal on both T1-and T2-weighted sequences with hyperintense foci on T2-weighted sequences, which may indicate fibrosis with glandular spots; (2) hypointense signal on T1-weighted and T2-weighted images with hyperintense foci on T1-weighted image, which is caused by haemorrhagic foci within the fibrotic tissue; and (3) hypointense signal in both T1-weighted and T2-weighted sequences if fibrotic reaction is abundant.…”
Section: Deep Infiltrating Endometriosis Of the Posterior-lateral Commentioning
confidence: 99%
“…The presence and location of each endometrial implant were recorded. Endometriotic implants were described as (i) hyperintense nodules on T1-weighted and fat saturated T1-weighted MRI images, irrespective of their appearance on T2-weighted MRI images (13)(14)(15) or (ii) hypointense nodules on both T1-and T2-weighted MRI images with signal intensity close to that of pelvic muscle (12) and Caramella et al (15).…”
Section: Mri Identification Of the Lesionsmentioning
confidence: 99%
“…However, more frequently, a fixed pelvis is caused by a benign disease, either severe endometriosis or severe adhesions with the bilateral tuboovarian complexes adherent to the pelvic sidewalls or from a large fibroid uterus associated with scar tissue or endometriosis [1,2].…”
Section: Introductionmentioning
confidence: 99%